The prevalence of internet gaming disorders and the associated psychosocial risk factors among adolescents in Malaysian secondary schools - Nor Firdous, Mohamed; Norhafizah, Ab Manan; Muhd Fadlin, Muhammad Firdaus Chan; Bahbibi, Rahmatullah; Rasidah, Abd Wahab; Siti Nor Amira, Baharudin; Priyalatha, Govindasamy; Kahar, Abdullah (SAGE Publications Inc., 2023)
Internet Gaming Disorder (IGD) has been placed under the conditions for further study segment in DSM-5. The purpose of the current study was to develop a preliminary psychosocial model as a reference for providing appropriate intervention, particularly for adolescents with IGD. A total of 5290 adolescents from secondary schools in seven states in Malaysia were recruited by using proportionate random sampling. A standardized set of validated questionnaires such as DASS-21, BIS-11, and IGDS9-SF were distributed to participants that fulfilled the inclusion criteria. The prevalence of IGD among Malaysian adolescents was 3.5%. The bivariate analysis summarized that factors such as stress, impulsivity, gender, time spent using the internet, and relationship with parents and friends; have statistically significant associations with IGD. The logistic regression model revealed that adolescents with IGD were 9 times more likely to experience extremely severe stress (p < 0.001). Several psychosocial factors were associated strongly with IGD in the current study, however, mental health shows the most significant issues among adolescents with IGD. Immediate intervention through a psychological approach to internet gaming is needed from parents, schools, and also respective stakeholders. IGD may become one of the addictions diseases that cause deterioration in many aspects of an adolescent’s future life without serious intervention.